All-optical intelligent computing three-dimensional sensing system and device - YAN TAO; FANG LU; DAI QIONGHAI; ZHOU TIANKUANG (2023)
The invention discloses an all-optical intelligent calculation three-dimensional sensing system and device, and the system comprises a reference light input module which is used for generating a laser beam; the all-optical structured light coding module is used for modulating a wavefront phase based on the laser beam so as to generate structured light of which a spatial mode changes along with depth; the structured light illumination module is used for irradiating the generated structured light to the surface of an object; the all-optical reflected light decoding module is used for performing light intensity mapping on depth information in the structured light reflected by the object on an output plane; and the three-dimensional information acquisition module is used for acquiring light intensity information on an output plane by using a photoelectric detector so as to perform depth information acquisition and realize three-dimensional perception. Depth information perception is achieved through the propagati